The Implementation of the Fun School Movement in Improving the Quality of Learning at SMP Sains Tebuireng - Hubaidi, Hubaidi (Journal Of Islamic Education And Pesantren, 2023)
Low learning motivation and academic achievement are problems that need to be addressed through appropriate solutions. Low learning motivation often leads to low academic achievement. One of the causes of students’ low motivation to participate in school learning is the lack of attractiveness of the school environment for learners. Ideally, schools should function as envisioned by Ki Hadjar Dewantara, namely as pleasant “gardens” for learning. This study, which employed a descriptive qualitative approach, aimed to explore the concept of the Joyful School Movement (Gerakan Sekolah Menyenangkan/GSM) and to examine the extent to which GSM management can enhance students’ learning motivation and academic achievement at SMP Sains Tebuireng. Through the implementation of Joyful School Movement management, schools are directed to become enjoyable places for learning knowledge and acquiring life skills so that students can develop into successful learners. The management of GSM—covering planning, organizing, actuating, and controlling—has been implemented effectively. In the short term, the establishment of five learning zones within classrooms has had a positive impact on improving students’ learning motivation and academic achievement. Continuous support and appreciation from the school community have also contributed to creating a conducive learning atmosphere in the school.